PENGENALAN INDENTITAS PENUTUR MENGGUNAKAN ALGORITMA DISCRETE WAVELET TRANSFORM (DWT) DAN HIDDEN MARKOV MODELS (HMM) - andi asni b; diah Patriana s (Lembaga Penelitian Universitas Balikpapan, 2018)
This study aims to build a speaker recognition system using the Discrete Wavelet Transform (DWT) algorithm and Hidden Markov Models (HMM). Speech signals from each speaker were recorded using Indonesian words